2001
DOI: 10.1098/rstb.2001.0894
|View full text |Cite
|
Sign up to set email alerts
|

Early effects of climate change: do they include changes in vector-borne disease?

Abstract: The world's climate appears now to be changing at an unprecedented rate. Shifts in the distribution and behaviour of insect and bird species indicate that biological systems are already responding to this change. It is well established that climate is an important determinant of the spatial and temporal distribution of vectors and pathogens. In theory, a change in climate would be expected to cause changes in the geographical range, seasonality (intra-annual variability), and in the incidence rate (with or wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
224
0
11

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 287 publications
(236 citation statements)
references
References 41 publications
1
224
0
11
Order By: Relevance
“…Only 13 years ago, it was concluded that there was no strong evidence to show that climate change was exerting a demonstrable impact on vector-borne diseases, such as malaria, dengue, leishmaniosis and tick-borne diseases (50). In spite of the large amounts of data being gathered, we are still a long way from knowing whether insects and other organisms are responding and adapting to climate change and if such changes apply widely across taxa, space and time (51).…”
Section: Climatic Factors and Culicoidesmentioning
confidence: 99%
“…Only 13 years ago, it was concluded that there was no strong evidence to show that climate change was exerting a demonstrable impact on vector-borne diseases, such as malaria, dengue, leishmaniosis and tick-borne diseases (50). In spite of the large amounts of data being gathered, we are still a long way from knowing whether insects and other organisms are responding and adapting to climate change and if such changes apply widely across taxa, space and time (51).…”
Section: Climatic Factors and Culicoidesmentioning
confidence: 99%
“…Much theoretical and empirical work has focused on the likely effects of climate warming on disease vectors (Martens et al 1999, Githeko et al 2000, Kovats et al 2001. It has been found that vector-borne pathogens are particularly sensitive to climate warming (Rogers and Randolph 2003).…”
mentioning
confidence: 99%
“…Aunque el cambio climático puede afectar la distribución y el comportamiento de enfermedades de diversa etiología, se considera que las enfermedades transmitidas por artrópodos -y los vectores mismos-son altamente sensibles a cambios en las condiciones climáticas (Kovats, et al, 2001). El cambio climático puede alterar la relación de un animal con parásitos y vectores.…”
Section: Las Enfermedades Parasitarias Y El Cambio Climáticounclassified
“…Adicionalmente, Kovats, et al (2001) presentan como requerimientos mínimos para aceptar una relación causal entre el cambio climático y los cambios en salud, los siguientes:…”
Section: Las Enfermedades Parasitarias Y El Cambio Climáticounclassified